2018
DOI: 10.1094/phyto-09-17-0306-r
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Botrytis cinerea: Interactions with Native Vineyard Yeasts from Washington State

Abstract: Native yeasts are of increasing interest to researchers, grape growers, and vintners because of their potential for biocontrol activity and their contributions to the aroma, flavor, and mouthfeel qualities of wines. To assess biocontrol activity, we tested 11 yeasts from Washington vineyards, representing isolates of Candida saitoana, Curvibasidium pallidicorallinum, Metschnikowia chrysoperlae, M. pulcherrima, Meyerozyma guilliermondii, Saccharomyces cerevisiae, and Wickerhamomyces anomalus, for ability to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…Additionally, different Aureobasidium isolates were recurrently found. Previous reports have described the biocontrol ability of certain Aureobasidium strains against certain postharvest decay pathogens like B. cinerea, but other strains can behave as opportunistic pathogens in apples and sweet cherries (Kim, 2014;Wang et al, 2018). Altogether, our data confirmed that fungal post-harvest decay pathogens were already present at the field not only prior to harvest, but also at very early stages of fruit development.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, different Aureobasidium isolates were recurrently found. Previous reports have described the biocontrol ability of certain Aureobasidium strains against certain postharvest decay pathogens like B. cinerea, but other strains can behave as opportunistic pathogens in apples and sweet cherries (Kim, 2014;Wang et al, 2018). Altogether, our data confirmed that fungal post-harvest decay pathogens were already present at the field not only prior to harvest, but also at very early stages of fruit development.…”
Section: Discussionsupporting
confidence: 86%
“…The epiphytic fungi living in plant tissues, particularly Aureobasidium (Ferreira-Pinto et al, 2006), Candida (Mewa-Ngongang et al, 2019), and Pichia (Mewa-Ngongang et al, 2019, play essential roles in disease control. Aureobasidium pullulans was used as a biocontrol agent against B. cinerea on grapes (Wang et al, 2018a). Certain fungal genera enriched in the B.O and A.O samples have been reported to exhibit protective functions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, P. kluyveri strain SEHMA6B has shown to be more effective against B. cinerea than the synthetic fungicides. Moreover, in 2019, Carmichael et al [ 81 ] evaluated the abundance and the diversity of yeast populations already known as natural antagonists of postharvest pathogens ( Aureobasidium , Cryptococcus , Rhodotorula , and Sporobolomyces ), with a particular focus on their action against B. cinerea , in the different phenological stages of table grapes (variety crimson seedless). The results of this study showed that a high presence of populations of possible biocontrol yeasts was associated with a low prevalence of pathogenic groups.…”
Section: Yeast Applications Against Pathogenic Fungi Of the Grape In Post-harvestmentioning
confidence: 99%